Analysis of Waste in Plastic Packaging Products Warehousing Activities Using a Lean Warehousing Approach - Clairine Aurellia Sanjaya; Dira Ernawati (ITEJ (Information Technology Engineering Journals), 2026)
The manufacturing industry is required to meet customer demands quickly and precisely in the midst of fierce competition, so efficient operations are needed. PT. XYZ as a plastic packaging manufacturer is facing inventory buildup due to the uncertainty of delivery schedules. This condition leads to various wastes, including excess capacity, product damage, and unnecessary movements, which ultimately increase lead time and reduce warehouse efficiency. This research intends to pinpoint inefficiencies in warehouse operations by employing a lean warehousing strategy with the WAM and VALSAT techniques, while suggesting enhancements through a 5W+1H analysis. The findings indicate that the dominant wastes are inventory (20,21%), overproduction (19,60%), and defects (17,24%). The improvement proposal is focused on improving inventory management through the implementation of a real-time-based barcode/RFID system, which is supported by standardization of work procedures, routine evaluation, layout optimization and determination of storage time limits. The proposed improvements were able to increase efficiency by reducing the processing time by 827 minutes, from 1.881 minutes to 1.054 minutes. The number of activities was also reduced from 43 to 35 activities. In addition, process efficiency has increased, as shown by an increase in Process Cycle Efficiency (PCE) by 1,59%, from 2,02% to 3,61% in warehouse operations